Identification by Raman spectroscopy of pararealgar as a starting material in the synthesis of amorphous arsenic sulfide pigments. (February 2018) - Vermeulen, Marc; Saverwyns, Steven; Coudray, Alexia; Janssens, Koen; Sanyova, Jana
Abstract: In this study, a combination of elemental analytical techniques (MA-XRF and SEM-EDX) were used to localize arsenic sulfide pigments within a 17 th -century Dutch painting and in the stratigraphy of an 18 th -century Flemish polychrome sculpture. Once located, Raman spectroscopy was used to obtain the vibrational signature of the arsenic sulfide pigments employed. By means of the latter analytical technique and due to the very distinctive Raman scattering signal of the various arsenic sulfide compounds, it was possible to identify the arsenic-based pigments as natural orpiment and amorphous arsenic sulfide. In the latter case, based on the minor bands observed and the good condition of the paint layers, it was possible to identify pararealgar, the orangey-yellow to yellow degradation product of realgar, as the initial arsenic sulfide material used for the synthesis of the amorphous pigment. To the best of our knowledge, this is the first time that combined pararealgar/amorphous arsenic sulfide Raman spectra are reported in historical samples. Therefore, this would be the first identification of pararealgar as the starting material to produce amorphous arsenic sulfide pigments used in artworks. Highlights: Raman spectroscopy is used to characterize amorphous and crystalline arsenic sulfide pigments found in works of art. Pararealgar is identified as the initial arsenic sulfide material used for the synthesis of the amorphous pigment. Partially sublimed pararealgar is identified in 17 th - and 18 th -century painting and polychrome sculpture.